Calcareous Nannofossils from the la Barca Formation (Paleocene/Eocene Boundary), Tierra Del Fuego, Argentina - Bedoya Agudelo, Erika Lorena; Olivero, Eduardo Bernardo; Concheyro, Andrea; Torres Carbonell, Pablo Juan; Martinioni, Daniel Roberto (Ameghiniana)
Deep marine Paleocene to Oligocene turbidites are exposed in several localities along the Atlantic coast of Península Mitre, Tierra del Fuego (Olivero and Malumián, 2008; Torres Carbonell et al., 2009). At Cabo Leticia (Fig. 1), the Paleocene sandstone-conglomerate package of the Cabo Leticia Formation is transitionally covered by the La Barca Formation, which consists of two members; a lower upper Paleocene sandstonemudstone dominated LB1 Member and an upper organic-rich mudstone-dominated LB2Member. At Punta Noguera (Fig.1), the La Barca Formation is interpreted to underlie lowermost Eocene turbidites of the Punta Noguera Formation (Olivero et al., 2002; Malumián, et al., 2009). The late Paleocene age of the lower LB1 Member of the La Barca Formation was initially established on the basis of foraminifera and dinocysts (Olivero et al., 2002; Malumián and Caramés, 2002). New studies at Punta Ainol (Fig. 1) have also found a diagnostic late Paleocene assemblage of calcareous benthic foraminifera contained in organic-rich mudstones interpreted as part of the LB2 Member, which suggests a late Paleocene age for the whole formation (Sample PT Sur, Torres Carbonell et al., 2009).Agglutinated foraminifera are dominant in the La Barca Formation, and only two isolated horizons preserve calcareous benthic foraminifera (Malumián and Jannou, 2010), whereas planktonic foraminifera and calcareous nannofossils have not been previously found in the formation (Malumián and Jannou, 2010). As part of ongoing research devoted to the study of calcareous nannofossils from Tierra del Fuego, we have analyzed samples from the La Barca Formation, both at its type locality in Cabo Leticia and from the mudstones exposed at Punta Ainol. None of the samples processed from the type locality of the La Barca Formation were fertile. Nevertheless, the organic-rich mudstones samples from Punta Ainol are fossiliferous and contain calcareous nannofossils that correlate with other Paleocene-Eocene assemblages from the Southern Hemisphere. Thus, the ...